Effects of Hemodialysis on Tei Index: Comparison between Flow Doppler and Tissue Doppler Imaging. Issue 10 (14th January 2015) - Gerede, Demet Menekse; Turhan, Sibel; Kaya, Cansin Tulunay; Ozcan, Ozgur Ulas; Goksuluk, Huseyin; Vurgun, Veysel Kutay; Dincer, Irem; Kutlay, Sim; Erturk, Sehsuvar; Erol, Cetin
<x xml:space="preserve">Abstract</x> Objective Myocardial performance index (MPI, Tei index) has been described as a noninvasive measurement of left ventricle (LV) function. Our aim was to investigate the influence of preload on the LV MPI obtained by pulsed‐wave tissue Doppler imaging (PWTDI) and determined by flow Doppler waveforms in patients with end‐stage chronic renal failure (CRF). The second aim of this study was to investigate the relationship between the Tei indices obtained by both methods. Methods Eighty‐four patients on regular hemodialysis (HD) treatment were included (mean age of 45.3 ± 14.5 years). Standard echocardiographic measurements, the Tei indices obtained by conventional flow Doppler and PWTDI methods, mitral inflow velocities, and mitral lateral annulus tissue Doppler velocities were measured immediately before and after hemodialysis. Results After HD, weight loss in patients was significantly revealed (predialysis 63.6 ± 13.3 kg; postdialysis 60.9 ± 13.0 kg; P < 0.001). Left ventricle and left atrium diameters were significantly decreased after HD. Transmitral E and A velocities decreased after HD. Although Tei index measuring by conventional flow Doppler method significantly increased, Tei index measuring by PWTDI did not change after HD. Conclusions The conventional flow Doppler‐derived LV Tei index is influenced by hemodialysis. However, PWTDI‐derived LV Tei index is not influenced by hemodialysis. The loading status of a patient should be taken into account during the application of the Tei index to the evaluation of myocardial performance.